Application of copper and aluminium electrode in electro coagulation process for municipal wastewater treatment: A case study at Karachi - Rafique, Lubna; Adnan, Anila; Taha, Anam; Bano, Shella; Vambol, Sergij; Mushtaq, Tahira; Ilyas, Nabila; Hussain, Shehnaz; Borysova, Larisa; Kovalov, Oleksandr (Ecological Questions, 2022)
The reuse of treated domestic wastewater is an imperative source of water for numerous purposes. The treatment of municipal wastewater can be process by utilizing the technique for electrocoagulation. Electrocoagulation (EC) is an eco-friendly technique that combines the functions and advantages of conventional coagulation, flotation, and electrochemistry in water and wastewater treatment. The aim of present study was to assess the potential of electrocoagulation process in removing COD, BOD, TSS, turbidity, sulphate, nitrate, chloride and TDS from municipal wastewater. This experimental study was carried out at a batch system by using copper and aluminium electrodes aiming to treat the municipal wastewater at (0, 7, 14, and 21 volts, 50mamp for 60minutes) from Sample Baloch Colony (SBC), Sample Rind Goth (SRG), Sample Cattle Colony (SCC), Sample Pakistan Machine Tool Factory (SPMTF) and Sample Mehran Highway (SMH). The results revealed that the maximum removal efficiency of COD 96% for SPMTF, BOD 38.5% for SPMTF, TSS 98.14% for SMH, Turbidity 95.7% for SPMTF, Sulphate 95.9% for SRG, Nitrate 95.23% for SMH, Chloride 97.92% for SMH and TDS 96.9% for SRG at 21 volt. The present study suggested that the treated wastewater could be safely reuse for lawns, parks, tree plantation and recreation purpose.